2016
DOI: 10.3168/jds.2015-10323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air exposure, temperature and additives on fermentation characteristics, yeast count, aerobic stability and volatile organic compounds in corn silage

Abstract: Ensiling conditions strongly influence fermentation characteristics, yeast count, and aerobic stability. Numerous volatile organic compounds including esters are produced, which may negatively affect feed intake and animal performance and air quality. In addition to a farm survey, 3 laboratory experiments were carried out to study the effects of air (by delayed sealing or by air infiltration during anaerobic storage), temperature (20 and 35°C), and various types of additives [blends of either sodium benzoate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 46 publications
12
65
1
5
Order By: Relevance
“…Weiss et al. () suggested that ethyl ester can also be directly produced by lactic acid bacteria (Liu & Siezen, ) or yeasts (Fredlund, Druvefors, Olstorpe, Passoth, & Schnürer, ; Nordström, ) and not only by the esterification of ethanol with a fermentation acid. They stated that it seems very likely that both chemical and biochemical processes are involved in forming esters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weiss et al. () suggested that ethyl ester can also be directly produced by lactic acid bacteria (Liu & Siezen, ) or yeasts (Fredlund, Druvefors, Olstorpe, Passoth, & Schnürer, ; Nordström, ) and not only by the esterification of ethanol with a fermentation acid. They stated that it seems very likely that both chemical and biochemical processes are involved in forming esters.…”
Section: Discussionmentioning
confidence: 99%
“…When these silages were exposed to air after opening, both ethyl ester concentrations decreased during exposure. Also, both ethyl esters showed a strong correlation with ethanol, highlighting the prominent role of ethanol in esterification (Weiss & Auerbach, ; Weiss et al., ). The immediate sealing of a silo leads to suppression of yeast growth.…”
Section: Introductionmentioning
confidence: 99%
“…The factors affecting the extent of aerobic deterioration act together in a complex process whereby interactions between the significant diversity of micro‐organisms can cause many variations (Weiss et al . ).…”
Section: Phases Of the Silage Fermentation Processmentioning
confidence: 97%
“…In developed countries, nitrogen oxide (NO x ) emissions from fertilizer and manure accounted for 27% of GHG emissions and CO 2 from all farm sources accounted for 21% of GHG emissions. Weiss, Kroschewski, and Auerbach (2016) and Brüning, Gerlach, Weiss, and Südekum (2018) found that elevated concentrations of VOC were associated with delayed silo sealing which was accompanied by increased ethanol and yeast counts. Differences in methods of crop storage did not appear to be specifically addressed in that analysis.…”
Section: Global Warmingmentioning
confidence: 99%